2022
DOI: 10.1109/tgcn.2022.3162649
|View full text |Cite
|
Sign up to set email alerts
|

Multiagent Reinforcement Learning-Based Signal Planning for Resisting Congestion Attack in Green Transportation

Abstract: Inefficient signal control will not only exaggerate traffic congestion, but also increase the fuel consumption and exhaust emissions. Thus, signal planning is highly important in green transportation. As the Connected vehicle (CV) technology has transformed today's transportation systems by connecting vehicles and the transportation infrastructure through wireless communication, the CV-based signal control system has seen significant studies recently. Unfortunately, existing signal planning algorithms in use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…In recent years, the transportation network of fresh agricultural products has undergone great evolution [2]. Low efficiency and high cost of distribution have always been problems in the logistics industry, especially in the terminal distribution process [3,4]. Studies have shown that the low efficiency and high cost of terminal distribution directly restrict the efficiency improvement of the entire distribution supply chain.…”
Section: Variables α I Distribution Center I Selection or Not δ Imentioning
confidence: 99%
“…In recent years, the transportation network of fresh agricultural products has undergone great evolution [2]. Low efficiency and high cost of distribution have always been problems in the logistics industry, especially in the terminal distribution process [3,4]. Studies have shown that the low efficiency and high cost of terminal distribution directly restrict the efficiency improvement of the entire distribution supply chain.…”
Section: Variables α I Distribution Center I Selection or Not δ Imentioning
confidence: 99%